Wonder Woman. Vol. 2, Sacrifice - King, Tom, 1978- (King, Tom, 1978-. Wonder Woman, 2024)
"Captured by a team of villains, Diana Prince finds herself up against the nemesis of our story, The Sovereign, wielding the Lasso of Lies. As her new adversary tightens the grip on Wonder Woman's psyche, will she prove victorious over the web of Amazon lies weaved in Man's World?"--